KEHIDUPAN SOSIAL–EKONOMI BURUH PEREMPUAN DI CV. RASDI & CO KOTA PADANG TAHUN 2000-2020 - Vanesha Oktavianza; Najmi Najmi (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
This article is a study of socio-economic history that discusses the development of the socio-economic life of women workers at the CV spice export factory. Rasdi & Co Padang City. This study aims to determine the development of the socio-economic life of women workers after working at CV. Rasdi & Co Padang City. This study uses historical methods consisting of heuristic, verification, interpretation, and historiography steps. The results of this study indicate that the lives of women workers can develop well, because the wages they earn are able to meet the daily needs of their families and can improve the education of their children. This can happen because companies often apply overtime and a contract system so that women workers can get additional income beyond their daily wages. So it can be concluded that this company has the goal of empowering women who want to work to help the family's economy without the requirement of a higher education certificate. However, during the Covid-19 pandemic this company was forced to take action to lay off old female workers for the safety of all workers and to maintain the continuity of the company in the midst of economic difficulties because spice export activities were temporarily stopped and only carried out spice delivery activities within Indonesia.